Cogas, janas e le altre: le creature mitiche e fantastiche nella letteratura e nel cinema sardi - Mereu, Myriam (Italianistica Debreceniensis, 2018)
Sardinian contemporary literature and films have recently recovered an extensive heritage of folk myths and legends taken from the oral tradition. Legendary figures, such as accabadoras (female figure who was enabled with the task of easing the sufferings of the dying people), and fantasy creatures, such as cogas, surbiles (‘vampire witches’), janas (‘fairies, pixies’), and panas (‘the ghosts of women who died in childbirth’) are being revived by writers and film directors with the purpose to bring their memory back to life and share it with a wide audience of readers and spectators.The analysis of imaginary and legendary creatures in Sardinian contemporary literature cannot overlook orality and its central role in shaping popular imagination over the centuries. Writing has replaced orality, whilst mass media and digital media are getting the upper hand over storytelling as a practice of community and family aggregation, meant to mark the long working hours and scare the children, amongst the most common functions of Sardinian oral storytelling. The literary corpus includes fairy tales, novels, tales and legends dealing with the Sardinian oral tradition, whilst on the cinematic side I will examine short films, feature films and documentaries made in Sardinia over the last fifteen years.